Fun Learning Through Quizizz Game in The PAI Student Media Development and Learning Resources Class - Yasid, Muhammad; Mulyadi, Mus (Samodra Ilmu: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2023)
How to bring about fun learning experience of PAI students through Quizizz Game in the Media Development and Learning Resources class is the main issue why this paper was written. In this a descriptive research study, the researcher use quantitative descriptive method. Questionnaires, observation schedules, and interview guides as measurement methods to collect data on student perceptions level on using Quizizz. Data students questionnaire was carried out using a saturation sampling method on total 22 student population. And interview to support and deepen the data on student perceptions and experiences regarding the use of Quizizz. The result shows, the level of perception and acceptance of PAI students in 4A class at the Faculty of Tarbiyah UIN Bengkulu towards the use of Quizizz shows a good level. This can be seen from several assumptions such as; Quizizz scoring is more fun; Prefer the assessment method with Quizizz over the usual method; Lectures are not rigid; Quizizz gets the class excited; Quizizz makes lectures more lively and active; and they agreed to recommend Quizizz over other courses.